Acute and Subchronic Toxicity Studies of Aristolochic Acid A in Tianfu Broilers - Dan Xu; Chonglin Ran; Lizi Yin; Juchun Lin; Hualin Fu; Xi Peng; Xiaoling Zhao; Gang Shu (Animals, 2021)
Aristolochic acid (AA) is one of the components of some traditional Chinese medicines, which has high toxic potential in animals, leading to huge economic losses in the breeding industry. The purpose of this study is to evaluate the toxicology of AA on Tianfu broilers through acute and subchronic toxicity tests. The results showed that the median lethal dose of AA to Tianfu broilers was 14.52 mg/kg. After continuous intraperitoneal injection of AA solution (1.452 mg/kg) for 28 days, the swollen and necrotic renal tubular epithelial cells were histologically observed; in addition, blood urea nitrogen (BUN) and creatinine (Cre) were significantly increased, indicating AA could induce serious kidney lesions in broilers. Moreover, the ROS, the apoptosis rate and the depolarization rate of the mitochondrial membrane potential of broilers’ renal cells increased. The results of QRT-PCR showed that AA reduced the mRNA expressions of HO-1, NQO1, Raf-1 and Bcl-2, while the expressions of Bax and Caspase-3 increased, which show that AA aroused oxidative stress and promoted the apoptosis of renal cells. In conclusion, AA has been found to damage broilers’ kidneys by breaking the redox balance to form oxidative stress, along with promoting apoptosis of renal cells.